DIFFERENT APPROACHES TO THE INTERPRETATION OF THE CONCEPT OF "PEDAGOGICAL PROFESSIONALISM" IN SCIENTIFIC RESEARCH (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the problem of variuos theoretical approaches to the definition of the notion "pedagogical professionalism" and its contents.
Keywords: the professionalism; the professional pedagogical activity; the pedagogical professionalism